2018
DOI: 10.1097/dcr.0000000000001196
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Impact of Hypochloremia in Patients With Stage I to III Colorectal Cancer After Radical Resection

Abstract: BACKGROUND: Recent studies have suggested that electrolyte disorders might be a negative prognostic factor for some diseases. OBJECTIVE: The purpose of this study was to systematically evaluate the prognostic role of electrolyte disorders in patients with stage I to III colorectal cancer who received radical surgical resection. DESIGN: This study was retrospectively performed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
2
7
0
Order By: Relevance
“…The authors found a higher in-hospital mortality in patients with electrolyte disorders compared to patients with normal electrolytes (8). In another investigation among 5,089 patients with colorectal cancer, hypochloremia was associated with a worse overall survival and shorter disease-free survival (9). This study detected hypochloremia to be an independent prognostic factor for OS and 1-YS in GBM patients and is well in line with previous results.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The authors found a higher in-hospital mortality in patients with electrolyte disorders compared to patients with normal electrolytes (8). In another investigation among 5,089 patients with colorectal cancer, hypochloremia was associated with a worse overall survival and shorter disease-free survival (9). This study detected hypochloremia to be an independent prognostic factor for OS and 1-YS in GBM patients and is well in line with previous results.…”
Section: Discussionsupporting
confidence: 91%
“…Several recent studies additionally suggest that electrolyte disorders might be associated with a worse prognosis in a variety of malignancies (8), e.g. in colorectal cancer (9), lung cancer (10) and lymphoma (11,12). To date, data on prevalence and eventual clinical impact of preoperative disturbances in serum electrolytes and renal parameters in GBM patients is scarce.…”
Section: Introductionmentioning
confidence: 99%
“…The authors found a higher in-hospital mortality in patients with electrolyte disorders compared to patients with normal electrolytes (8). In another investigation among 5,089 patients with colorectal cancer, hypochloremia was associated with a worse overall survival and shorter disease-free survival (9). This study detected hypochloremia to be an independent prognostic factor for OS and 1-YS in GBM patients and is well in line with previous results.…”
Section: Discussionsupporting
confidence: 87%
“…Several recent studies additionally suggest that electrolyte disorders might be associated with a worse prognosis in a variety of malignancies (8), e.g. in colorectal cancer (9), lung cancer (10) and lymphoma (11,12). To date, data on prevalence and eventual clinical impact of preoperative disturbances in serum electrolytes and renal parameters in GBM patients is scarce.…”
Section: Introductionmentioning
confidence: 99%
“…It is a great honor to comment on the article entitled "Prognostic impact of hypochloremia in patients with stage I to III colorectal cancer after radical resection" by Qingguo Li and his colleagues in the Diseases of Colon and Rectum (1).…”
mentioning
confidence: 99%